XENOPHOBIC ATTITUDES AND REPRESENTATIONS IN SOCIAL MEDIA DURING COVID-19 PANDEMIC IN INDIA - Jochan, Grace Maria; Chakraborty, Rituparna; Arur, Aditi (Revista Conhecimento Online: Diversidade e Inclusão Social, 2022)
Social media activity was reported to have significantly increased during the pandemic period as most of the daily routines transformed into the digital space. This paper attempted to explore the politics of representation in digital space using Foucauldian theories of power and discipline. A qualitative exploration of the xenophobic attitudes and representation was conducted on 123 young adults to understand how health concerns associated with the pandemic influenced social representations and marginalization of certain social sections and how participants recognized and understood their contribution to this group polarization. Thematic analysis of participant opinions indicated a significant change in polarization and attitude towards out-groups following the pandemic outbreak. The existing hierarchical homogenization and polarization of the marginalized moderated by polarized political affinities were found to be translated into digital space intensifying xenophobic attitudes thereby contributing to the evolution of new digital cultures and hierarchies in digital literacy.